Assessment of stable isotopes and elemental composition at three different ages of Mangrove Forest in Matang, Malaysia - Razzaq, Khan Waseem (2019)
Matang Mangrove Forest Reserve (MMFR) is considered as one of the most productive and best-managed mangrove forest in the world. However, in the last few decades, there have been concern on the issues of productivity in MMFR and few field-based studies based on timber volume, density and biomass have been performed to assess its productivity. This study also attempts to assess the productivity using stable isotopes (δ15N and δ13C) and selected elemental composition. This study was the first to use stable isotopes and elemental composition to determine the productivity in mangrove forest of Malaysia and the factors which effect on productivity. In order to do that, four main objectives were outlined, namely; (1) to investigate the productivity of different aged-stands (compartment) with nutrients productivity model using stable isotopes with salt stress and nutrient abundancy, (2) to identify elemental concentrations and stable isotope ratios in inter- and intra-mangrove species stands along the inundation gradient of the mangrove forest, (3) to compare elemental concentration between similar and different aged stands, (4) to study the heavy metal concentration in the sediment using contamination indices (pollution load index, geoaccumulation index and contamination element or part and hazard assessment code) For objective 1: 90 samples of leaves from R. apiculata trees collected from six compartments (Compt. 18, 31, 71, 74, 42 and 55) and run for analysis. The selection of these compartments was based on age and management as discussed earlier. Sixteen variables; stable isotopes (δ13C, δ15N), macronutrients (C, N, P), cations (Ca, Mg, Na, K) and trace elements (Cd, Cu, Fe, Mn, Pb, Zn) were analyzed and fitted into established productivity equation. To validate the model, productivity using biomass estimation also were performed in study plot of 10m x 10m within five managed sites namely, Compt. 18, 31, 71, 74 and 67. Results show that in the 15 year-aged stands, Compt. 18 showed higher productivity than in Compt. 31; for the 25 year-aged stands, Compt. 74 has higher productivity than Compt. 71; but mean biomass of two 25-year compartments was higher than the mean biomass of the two 15-year compartments. It can be concluded from the models that even with similar aged-stand, there is a variation in terms of productivity. Interestingly, the trend for biomass estimation produced similar results that can be validated by productivity models in which similar aged stand showed different value of productivity. To investigate variation in productivity between same age and different age compartments following studies were conducted. Different species of mangroves i.e., Avicennia alba, Rhizophora. apiculata, Bruguiera parviflora and Sonneratia ovata in different compartments (Compt. 39, 40, 30 and 18) were analysed to achieve objective (2): trace elements (Mn, Fe, Cu, Zn), cations (Na, K, Ca, Mg) and stable isotope (δ13C and δ15N) ratios were found to follow different patterns along the inundation gradient in the leaves of the sampled plant species. Elemental concentrations of Na, K, Fe, Cu, Zn and Mn along with stable isotopic ratio were found differed significantly within similar and different mangrove species. For achieve objective (3): nutrients concentrations were examined in leaves, root and sediment of Rhizophora apiculata stand in six compartments with different aged (Compt. 18 and 31=15-year-old stand; Compt. 71 and 74 = 25-year-old stand; Compt. 42 and 55= virgin jungle reserve) were collected and analysed. Results show that nutrient concentrations between all stands on average were similar and can be arranged collectively as Ca>Na>Fe>K>Mn>Mg>Zn>Cu>Pb>Cd and C%>N%>S%>P%. Concentrations of Cu, Cd, Pb, Mn and Zn were found at high range that indicating heavy metal pollution most probably due to human activities. The ratio of δ15N showed positive values and could be translated as there was no deficiency of N element. Ratio of δ13C on the other hand, showed more negative values indicating that there is less salinity stress in all studied areas, the fourth (4) objective: sediment samples were collected at the depth of 7cm and analyzed for assessing heavy metal contamination in six compartments (Compt. 18, 31, 42, 71, 74 and 55). High concentrations for Cu, Ni and Cd were observed in Compt. 42 while Compt. 18 and 74 had higher Zn and Pb concentrations, respectively. Assessment shows that all six compartments are categorized from low to moderate polluted areas. Geo-accumulation index (I-geo), pollution load index (PLI) and contamination factor (CF) classified the compartments in low contaminated area. Our findings also suggested R. apiculata as a suitable candidate for bioremediation of heavy metal-contaminated sediments and for restoration of degraded ecosystem with high levels of heavy metal contamination. In conclusion there is no prominent increase in biomass with age. This suggests that Rhizophora apiculata is not showing high productivity.